PERAN KEPUASAN PELANGGAN MEMEDIASI PENGARUH KUALITAS LAYANAN TERHADAP WORD OF MOUTH PADA PELANGGAN KLINIK KECANTIKAN - Putri, Luh GD Devani Astrid Wira; Sri Suprapti, Ni Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
This study aims to explain the effect of service quality on word of mouth, service quality on customer satisfaction, satisfaction with word of mouth, customer satisfaction in mediating the effect of service quality on word of mouth, and examine differences in the level of service quality, customer satisfaction, and word of mouth. mouth between the beauty clinic Natasha Skin Care and Erha Clinic. Data were collected online using a questionnaire from 100 customers of two beauty clinics in Denpasar City, then analyzed using path analysis. The results of this study indicate that service quality has a significant and positive effect on customer satisfaction, service quality has a significant and positive effect on word of mouth, customer satisfaction has a significant and positive effect on word of mouth, customer satisfaction is able to partially mediate the effect of service quality on word of mouth. mouth. There is no difference between Natasha Skin Care and Erha Clinic in terms of service quality, customer satisfaction and word of mouth